Building Self-Confidence among Elementary Students in Parepare City through a Social-Educational Intervention Program - Musfirah, Musfirah; Burhan, Imron; Amran, Muhammad; Iyan, Iyan; Alfatih, Ainun Najib (PT Agung Media Publisher, 2025)
Self-confidence plays a vital role in children’s psychological development and influences their academic, social, and emotional achievements. However, many elementary school students struggle with low self-confidence, which can hinder their learning motivation and personal growth. This community service program was conducted at UPTD SD Negeri 5 Parepare to enhance students’ self-confidence through a social-educational intervention. The program was designed with three stages: preparation, implementation, and reflection. Activities included interactive and reflective learning experiences adapted to the students’ developmental levels. The materials addressed self-awareness, setting realistic goals, positive self-talk, stepping out of the comfort zone, maintaining appearance, building positive social environments, and learning from experiences. The implementation revealed significant improvements in students’ engagement, self-expression, and self-awareness. Pre- and post-activity reflections indicated that students became more confident in participating, expressing ideas, and interacting with peers. The findings suggest that integrating social and educational strategies into character education can effectively foster self-confidence among elementary students. This program demonstrates the potential of social-educational interventions to strengthen personal growth and learning motivation in young learners.